Redescription of the goby Glossogobius tenuiformis Fowler, 1934 (Teleostei: Gobiidae) and assignment of Oman Glossogobius populations: a morpho-molecular approach - Jufaili, Saud M. Al; Esmaeili, Hamid Reza; Sayyadzadeh, Golnaz; Masoumi, Amir Hassan; Larson, Helen K. (Zootaxa, 2022)
Glossogobius giuris was originally described as Gobius giuris from the Ganges River, India. However, based on the uncertainty of its type locality and its apparent widespread distribution, a comprehensive study is being carried out to define the correct taxonomic status of this taxon. The South African population of the Glossogobius from St. Lucia Lake, KwaZulu-Natal was described as Glossogobius tenuiformis by Fowler in 1934. It has usually been considered as Glossogobius giuris but Hoese and Hammer indicated that it was a distinct species (2021: 83). Here, based on morphological characters and a molecular data set, we redescribe Glossogobius tenuiformis and assign the Oman populations of Glossogobius to this species. Glossogobius tenuiformis is distinguished from G. giuris by the absence or very short (and often only a few papillae long) sensory papilla line 6; presence of single rows of the sensory papillae in each cheek line, 12–16 pre-dorsal scale counts, and 1+1+9–11, usually 1+1+10, gill rakers on outer face of first arch. Glossogobius tenuiformis is also distinguished by molecular characters. Glossogobius tenuiformis shows 16% genetic distance with other members of this species complex, that includes G. laticeps from Vietnam, Bangladesh and China, G. giuris from South Africa and India and “giuris C” from India, Myanmar, Nepal, Bangladesh and Vietnam, and the highest genetic distance (24%) with G. circumspectus.